2014
DOI: 10.1108/amhid-02-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Support workers’ mental health knowledge and confidence in relation to exposure, experience, work setting and training

Abstract: Purpose -Previous studies have shown that support workers often have difficulties in recognising mental health problems in service users with intellectual disabilities. In the context of improved UK training programmes, the purpose of this paper is to explore the factors that can predict support workers' knowledge and confidence in this respect. Design/methodology/approach -In total, 80 support workers (40 residential and 40 community-based) completed a questionnaire about their length of work experience, expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…This could be incompatible with the important role the staff play in monitoring the health status of people with ID and in identifying early symptoms or problems to improve the quality of life for this frail population. Several studies reported challenges such as lack of knowledge, skills, misunderstanding and miscommunication which leads to lack of confidence in care delivery among people with ID in residential arrangements (Ann & Helena, 2014;Costello et al, 2007;Innes et al, 2012;Kåhlin et al, 2016;Quigley et al, 2001). This highlights the importance of training the residential social care workers in terms of frailty and health issues of people with ID (Northway et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This could be incompatible with the important role the staff play in monitoring the health status of people with ID and in identifying early symptoms or problems to improve the quality of life for this frail population. Several studies reported challenges such as lack of knowledge, skills, misunderstanding and miscommunication which leads to lack of confidence in care delivery among people with ID in residential arrangements (Ann & Helena, 2014;Costello et al, 2007;Innes et al, 2012;Kåhlin et al, 2016;Quigley et al, 2001). This highlights the importance of training the residential social care workers in terms of frailty and health issues of people with ID (Northway et al, 2016).…”
Section: Discussionmentioning
confidence: 99%